Diagnostic Accuracy of Point of Care Ultrasound (POCUS) for Diagnosing Neonatal Pneumothorax Keeping Chest X-ray as Reference Standard: POCUS: Neonatal Pneumothorax Keeping Chest X-ray as Reference Standard - Khan, Sara; Aziz, Sadaf; Ahmad, Asad Maqbool; Ayub, Hira; Naqvi, Syeda Fatima Ali; Kazmi, Syed Awais Haider (Pakistan Journal of Health Sciences, 2026)
Neonatal pneumothorax needs immediate medical assessment because it poses a danger to life. Neonates face radiation risks from chest X-ray (CXR), which physicians frequently use, but it creates treatment delays. Point-of-care ultrasound (POCUS) offers a rapid, bedside, radiation-free alternative. Objective: To assess how accurately POCUS detects neonatal pneumothorax compared to CXR, which serves as the standard reference. Methods: The descriptive, cross-sectional study took place in the Combined Military Hospital's Neonatal Intensive Care Unit from October to December 2025 after researchers obtained permission through ethical approval (Ref No. 576/2024). The study enrolled one hundred neonates who were 28 days old or younger and showed clinical signs of pneumothorax. A trained radiologist performed bedside POCUS using a high-frequency linear probe. A radiologist who remained blinded to the study read the CXR results. Researchers computed sensitivity, specificity, PPV, NPV, and overall accuracy together with ROC-AUC values. Results: CXR confirmed pneumothorax in 35 neonates. POCUS showed sensitivity 91.6%, specificity 93.75%, PPV 89.18%, NPV 95.2%, and overall diagnostic accuracy 93%. The AUC measurement reached 0.93 while the 95% confidence interval ranged from 0.87 to 0.97. Conclusion: POCUS provides high diagnostic accuracy which makes it an effective NICU screening tool for detecting neonatal pneumothorax.